PENILAIAN KINERJA SISWA UNTUK MENEMUKAN SIFAT PERSEGI DI KELAS VII SMP NEGERI 28 SURABAYA: Performance assessment, the properties of a square, learning media - Prayitno, Lydia Lia (Buana Pendidikan, 2010)
Performance assessment is one alternative assessment can be done by teachers during the learning process. In this research, performance assessment carried out to discover the properties of a square by using learning media. Media that used in this research are square from asturoÃƒâ€šÃ¢â‚¬â„¢s paper. Task students in groups to identify the properties of the square. Instrument that used in this research is the observation studentÃƒâ€šÃ¢â‚¬â„¢s performance. Data were analyzed by summing the scores given by observers. The result is the performance of students in discovering the properties of a square is in Ãƒâ€šÃ¢â‚¬Å“goodÃƒâ€šÃ¢â‚¬Â category. This means that students work on tasks assigned to the worksheet that given by teacher and accordance with the instructions given on the worksheets.